Através do cosmos : uma proposta lúdica para o ensino de astronomia e física - Silva, Paulo José Meira da (2014)
The knowledge of the high school students on the various topics of Astronomy today is worse than expected. This study aims to investigate the current level of knowledge in Astronomy of high school students from a public school in the city of Pirassununga, São Paulo, and create an alternative learning situation to contribute to this learning. The choosen tool was the ludic activity titled Através do Cosmos. The challenge is to create a profitable and fun activity by instigating students to solve problems and act socially. To this didactic sequence, a diagnosis questionnaire was initially applied to ascertain the students' prior knowledge. Next, the students were subjected to a cycle of lectures, finished with another questionnaire. Finally the ludic activity was applied in groups of three or four students. After the cycle of games, an assessment which was asked the students' opinions regarding the activity was performed. The results showed that, due to some difficulties during the process, the knowledge acquired by them was less than expected, but the ludic activity was a success among students and showed that it has potential for future applications and enhancements.